Real-Time Optimal Scheduling Model for Transit System with Flexible Bus Line Length. Issue 4 (April 2019) - Pei, Mingyang; Lin, Peiqun; Ou, Junfeng
We propose a new structured transit system with flexible bus line length based on the real-time requests of passengers. This operation mode can meet the travel demands of passengers (lower travel-time cost) and reduce the number of unnecessary stops (without boarding or alighting activities). We then compare the performance of the proposed transit system with that of fixed-route transit service and show the pros and cons of each system for several passenger demand levels. It is found that at low-to-moderate demand levels, the proposed flexible-route system tends to provide the lowest total travel time. In comparing a real-world deployment of the system in Guangzhou with comparable alternative system states, the optimization of the former is evident in idle and tidal modes, in which the total travel times reduced by more than 10%. Moreover, this operating system can achieve enhanced performance with the development of automated vehicle technology in the future.